Frequency of Celiac Disease Diagnosed on Endoscopic Duodenal Biopsy in Patients of Functional Dyspepsia - Muhammad Iftikhar Yousaf, Humaira Mubeen Afzal, Usama Faizan, Muhammad Haroon Yousaf, Muhammad Asif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of celiac disease diagnosed on endoscopic duodenal biopsy in patients presenting with functional dyspepsia. Methods: This was a cross-sectional study was conducted at the Department of Gastroenterology and Hepatology, Shalamar Medical and Dental College, Lahore. A total 160 patients of either gender, aged 20-70 years and diagnosed with functional dyspepsia were included. The study was conducted during a period of six months from September 2021 to February 2022. The informed consent of patients was obtained. All the basic demographic information of each patient was noted and all the patients underwent endoscopic duodenal biopsies and specimens were sent to the department of histopathology for the histopathological assessment of celiac disease. The collected data were analyzed statistically by using SPSS version 12. Results: Average age of male and female patients was 45.61±14.41 and 39.83±14.91 years. Among 160 patients 60(37%) were male and 100(63%) were females. There were 90(56.3%) patients who had dysmotility like dyspepsia, 54(33.8%) patients diagnosed with an ulcer like dyspepsia and 16(10%) patients were having unspecified dyspepsia. According to the Marsh classification, 140 patients were diagnosed with type-0, 7 patients with Type-1, 2 patients with type-2, 9 patients with type-3a and 2 patients with type-3b. Celiac disease was diagnosed with the help of Modified Marsh classification. Among 160 patients 13(8%) were diagnosed with celiac disease. Conclusion: The results of the current study show a high frequency of celiac disease in patients with functional dyspepsia. Keeping this fact in mind, silent/subclinical CD should be kept in mind as a cause of functional dyspepsia during clinical activities